Improving care for immigrant women before, during, and after childbirth - what can we learn from regional interventions within a national program in Sweden? - M. E. Nyström; E. C. Larsson; K. Pukk Härenstam; S. Tolf (BMC, 2022)
Abstract Background Migration has increased the number of immigrant women in western countries, which has led to a need to adapt sexual and reproductive health (SRH) care to a larger variety of experiences. Examples of problems are poor access/utilization of SRH services among migrants and a comparatively higher rate of mortality and morbidity in relation to pregnancy, especially among those from low- and middle-income settings. Attempts to improve SHR care must consider the complexity of both the problem and the system. A national program to improve women's health in Sweden provided opportunities to study interventions aimed at immigrant women, using a complexity theory lens. The purpose was to explore the characteristics and complexity of regional interventions aiming to improve care and health of immigrant women before, during and after childbirth, and provide knowledge on how regional healthcare actors perceive and address problems in these areas. Methods This archival research study is based on qualitative data from detailed yearly reports of all regional program interventions (n = 21 regions) performed between January 2017 and January 2019. The archival data consists of the regional actors' answers to an extensive questionnaire-like template, where the same questions were to be filled in for each reported intervention. Data analyses were performed in several steps, combining classic and directive content analysis. Results Six problem categories were addressed by 54 regional interventions, 26 directed at immigrant women and their families, 11 at healthcare staff, and 17 at the organizational system. The simple level interventions (n = 23) were more unilateral and contained information campaigns, information material and translation, education, mapping e.g., of genital mutilation, and providing staff and/or financial resources. The complicated interventions (n = 10) concerned increasing communication diversity e.g., by adding iPads and out-reach visits. The complex interventions (n = 21), e.g., health schools, integration of care, contained development, adaptions, and flexibility with regards to the immigrant women's situation, and more interaction among a diversity of actors, also from the wider welfare system. Conclusions It is important that complex problems, such as ensuring equal care and health among a diverse population, are addressed with a mix of simple, complicated, and complex interventions. To enhance intended change, we suggest that pre-requisites e.g., communication channels and knowledge on behalf of immigrant women and staff, are ensured before the launch of complex interventions. Alternatively, that simple level interventions are embedded in complex interventions.